Strengthening development : the interplay of macro- and microeconomics (ECLAC SantiagoCL, 1996)
Presents an assessment of the economic reforms undertaken to date. Offers some reflections on the direction that ongoing reforms should take, in the Secretariat's view. Focuses on the twin goals of securing economic stability while at the same time stimulating growth.
DC